2017
DOI: 10.1371/journal.pone.0184508
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size and proliferative marker geminin rather than Ki67 expression levels significantly associated with maximum uptake of 18F-deoxyglucose levels on positron emission tomography for breast cancers

Abstract: It has been well established that maximum standardized uptake value (SUVmax) for 18F-fluorodeoxyglucose positron-emission tomography/computed tomography (FDG PET/CT) is clinically useful for evaluating treatment efficacy as well as predicting prognosis of breast cancer patients. Although SUVmax reflects increased glucose uptake and metabolism possibly induced by activation of growth factor signaling or TP53 dysfunction, tumor characteristics of SUVmax-high breast cancers remain to be elucidated. For the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…This effect is possibly due to the increased glucose uptake in highly proliferative cancers, resulting in high levels of SUVmax. Consistent with our findings, a high 18 F-FDG avidity (SUVmax) was reported to be significantly associated with a high Ki67 index in breast cancer [ 36 37 38 ], gliomas [ 39 ], and lymphoma [ 40 ]. When analyzing different histological subtypes, we found that better-differentiated lung adenocarcinoma (papillary, acinar, lepidic adenocarcinoma, and variant adenocarcinoma) had a better correlation between Ki67 and PET semi-quantitative parameters than more poorly differentiated ones (micropapillary and solid predominant adenocarcinoma).…”
Section: Discussionsupporting
confidence: 89%
“…This effect is possibly due to the increased glucose uptake in highly proliferative cancers, resulting in high levels of SUVmax. Consistent with our findings, a high 18 F-FDG avidity (SUVmax) was reported to be significantly associated with a high Ki67 index in breast cancer [ 36 37 38 ], gliomas [ 39 ], and lymphoma [ 40 ]. When analyzing different histological subtypes, we found that better-differentiated lung adenocarcinoma (papillary, acinar, lepidic adenocarcinoma, and variant adenocarcinoma) had a better correlation between Ki67 and PET semi-quantitative parameters than more poorly differentiated ones (micropapillary and solid predominant adenocarcinoma).…”
Section: Discussionsupporting
confidence: 89%
“…So, a very wide spectrum of correlation coefficients between SUV max and Ki-67 was reported. Furthermore, most studies investigated small samples ranging from 6 to 75 patients/tumors and only four studies investigated samples over 100 patients [20] , [33] , [34] , [38] . Therefore, the reported data cannot be considered as evident.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, glucose metabolism might be stronger associated with other proliferation factors than with Ki-67. In fact, Nishimukai et al showed that SUV max correlated stronger with proliferation marker geminin than with Ki-67 [38] . The authors also suggested that geminin is preferable to Ki-67 evaluating the proliferative activity of breast cancer cells [38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography ([18F]-FDG PET/CT) is currently recommended by the National Comprehensive Cancer Network (NCCN) guidelines for disease staging [5,6] and might also provide significant prognostic information [7,8]. Tumor glucose metabolism assessed by the maximum standardized uptake value (SUVmax) is used as a surrogate of tumor aggressiveness and tumor cell proliferation [9,10]. Several studies have demonstrated the prognostic value of SUVmax of the primary breast tumor and/or regional lymph nodes measured on [18F]-FDG PET/CT in nonmetastatic breast cancer [11][12][13].…”
Section: Introductionmentioning
confidence: 99%